2008
DOI: 10.1002/lary.20021
|View full text |Cite
|
Sign up to set email alerts
|

The effect of multilevel upper airway surgery on continuous positive airway pressure therapy in obstructive sleep apnea/hypopnea syndrome

Abstract: In this study, most patients who had persistent symptoms of OSAHS after multilevel UAS did not have significant mouth leak that would preclude CPAP therapy. In this cohort of patients, CPAP pressure setting as well as compliance was significantly improved postoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 10 publications
1
36
0
2
Order By: Relevance
“…As previously mentioned, 10 cm H 2 O was enough to effectively address many of the cases where oropharyngeal collapse was noted, but in this case a higher pressure was required to open up the airway. This case is important because it provides direct evidence of how surgery can serve as a tool to improve CPAP compliance by helping reduce CPAP pressure, which supports the evidence already presented by previous studies …”
Section: Discussionsupporting
confidence: 85%
“…As previously mentioned, 10 cm H 2 O was enough to effectively address many of the cases where oropharyngeal collapse was noted, but in this case a higher pressure was required to open up the airway. This case is important because it provides direct evidence of how surgery can serve as a tool to improve CPAP compliance by helping reduce CPAP pressure, which supports the evidence already presented by previous studies …”
Section: Discussionsupporting
confidence: 85%
“…Eight studies were excluded due to lack of a comparison of pre- and postoperative CPAPs in patients after UAS. Of the 11 studies that met the inclusion criteria, 5 were retrospective [8,16,17,18,19], 4 were prospective [20,21,22,23], and 2 were RCTs [24,25]. UAS performed in the studies included nasal valve repair, radiofrequency ablation to the palate, turbinate reduction, septoplasty, Pillar implants, tonsillectomy, and UPPP.…”
Section: Resultsmentioning
confidence: 99%
“…Even though improved nasal breathing does not consistently improve OSAS itself, it can reduce daytime sleepiness and snoring [11-13]. Nasal obstruction usually causes mouth breathing during the day and night, which compromises adherence to CPAP therapy [14].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported that air leaks at a lower CPAP level and reduction in the maximal level of pressure can be tolerated in the patients with uvulopalatopharyngoplasty (UPPP) compared with those who have not [16,17]. On the contrary, more recent studies have reported an improvement in CPAP use after multilevel surgery for OSAS [11,18]. We found that patients with a history of upper airway surgery for OSAS or nasal obstruction use the CPAP machine significantly longer compared with those who have not undergone surgery.…”
Section: Discussionmentioning
confidence: 99%